DO BOARD CHARACTERISTICS AFFECT PROFITABILITY? EVIDENCE FROM PUBLIC SECTOR BANKS IN INDIA - TALUKA, SHWETA; VERMA, SUHASINI; SHARMA, JEEVESH (International Journal of Psychosocial Rehabilitation, 2020)
-The focus of this paper is to analyze the relationship between board structure and performance of 21 public sector banks (PSUs) in India. We have used the panel data analysis to study the relationship between the board characteristics and profitability of public sector banks. The time period of the study is from the year 2013-2018, covering the most recent period of time after amendments in the Companies Act, 2013 regarding the structure of the board. The board structure is one of the most important factors of corporate governance mechanism that plays a major role in the decision making of the firm. Therefore, the present study tries to find out the impact of board structure including major variables such as total board size, number of independent directors in the board and women directors, on the profitability of public sector banks. The study has used secondary data from the annual reports of concerned bank. It is an analytical paper which uses accounting approach to measure Return on Asset (ROA) and Return on Equity (ROE) as major performance indicators. The result finds a significant impact of board size on the performance of banks while there is no significant impact of number of independent directors and women directors on the performance of the public sector banks.